Is monetary policy overburdened? - Athanasios Orphanides (Federal Reserve Bank of Boston, 2013)
Following the experience of the global financial crisis, central banks have been asked to undertake unprecedented responsibilities. Governments and the public appear to have high expectations that monetary policy can provide solutions to problems that do not necessarily fit in the realm of traditional monetary policy. This paper examines three broad public policy goals that may overburden monetary policy: full employment; fiscal sustainability; and financial stability. While central banks have a crucial position in public policy, the appropriate policy mix also involves other institutions, and overreliance on monetary policy to achieve these goals is bound to disappoint. Central Bank policies that facilitate postponement of needed policy actions by governments may also have longer-term adverse consequences that could outweigh more immediate benefits. Overburdening monetary policy may eventually diminish and compromise the independence and credibility of the central bank, thereby reducing its effectiveness to preserve price stability and contribute to crisis management.
Keywords: E50; E52; E58; 330